POTENTIAL THERAPEUTIC EFFECT OF ANTI-DENGUE MEDICINAL PLANTS: A DETAILED REVIEW - Sadia Bano; Syed Zahoor ul Hassan Zaidi; Farooq Hassan; Madiha Khan Niazi; Sameea Haider; Bareera Sana; Muhammad Umer; Asmat Ullah Khan; Sobia Naeem (International Journal of Contemporary Issues in Social Sciences, 2024)
One of the viral infections spread by mosquitoes that is quickly infecting people is dengue fever. Particularly in tropical and subtropical areas of the world, it has high mortality and morbidity rates. The question of whether dengue infection is endemic in Guangdong has been brought up because dengue has been a continuous pandemic in Guangdong from its initial outbreak in Foshan, Guangdong province, China, in 1978. The study’s entire foundation is made out of secondary data sources, including relevant publications, governmental bodies, and related papers. Due to the dramatic rise in cases, complications, and severity, there may be an epidemic danger. Aedes is the name of the species of mosquito that transmits dengue. Depending on how severe they are, medical symptoms can be anything from trivial to fatal. Only a few of the many variables that affect the dengue virus’s ability to spread include topography, rainfall, temperature, rapid urbanization, and globalization. Due to its rapid global development, the lack of a specific treatment, an accessible technology for early infection diagnosis, and an effective vector control system, it is a problem of the utmost concern for public health. Dengue treated with numerous herbs some of these are explained in this manuscript.